Hubungan Syukur dan Sabar terhadap Kesejahteraan Subjektif pada Remaja - Farra Anisa Rahmania; Syarifah Na’imi Anisa; Putri Tri Hutami; Muhammad Wibisono; Ahmad Rusdi (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2019)
The current research revealed if patience and gratitude have the positive significant correlation with subjective well-being. Abdullah bin Mas’ud said iman has divine by patience and gratitude. The objective of this study is to investigate the correlation between gratitude, patience and subjective well-being of adolescent, and which one had the best correlation into subjective well-being. Total 164 adolescents participated in this study. Statistical analysis showed that both patience and gratitude had a positive significant correlation with subjective well-being. Patience has the best correlation with subjective well-being than gratitude. Factor analysis shows that gratitude has the better correlation to positive affect than patience, but patience has the better correlation with negative affect and life satisfaction than gratitude.